Modulation by steroid hormones of a ''sexy'' acoustic signal in an Oscine species, the Common Canary Serinus canaria - Rybak,Fanny (2004)
The respective influence of testosterone and estradiol on the structure of the Common Canary Serinus canaria song was studied by experimentally controlling blood levels of steroid hormones in males and analyzing the consequent effects on acoustic parameters. A detailed acoustic analysis of the songs produced before and after hormonal manipulation revealed that testosterone and estradiol seem to control distinct song parameters independently. The presence of receptors for testosterone and estradiol in the brain neural pathway controlling song production strongly suggests that the observed effects are mediated by a steroid action at the neuronal level.